Ecological Element in Oral Literature Wayang Jek Dong Malang Style - Astrid Wangsagirindra Pudjastawa; Yudit Perdananto (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2022)
Literature as part of the representation of human life is always tied to human culture nd environment. The problems raised by writers in literary works are part of the relity that occurs in the environment where they live. No exception with oral literature. As a traditional literary genre, oral literature has a depedence on ecological elements that exist in the universe. Plants an animals, for example, have a role in the literary context as part of the universe. Plants and animals, for example, have a role in the literary context as part of the puppetry element of the wayang Jek Dong Malang style. Oral literature contained in pupetry jek dong malangan style, for example, in practice by the puppeteer always involves ecological elements. Through the study of an ecocritical perspective, it can be seen that the presence of oral literture in Malangan style jek dong puppetry is always thick in the image of nature such as Pandawa Tani, Wader Bang Sisik Kencana, Wedus Putih Ngamen, and so on. The involvement of thes ecological elements shows a strong image of the nature, and culture of the Malang people.